(untitled) (Medico Legal Update, 2019)
Sex-related offenses are universal incidents, which are captivating in every stage of the society. Child sexual assault is a state of maltreatment meted out to a person below the age of eighteen and is matter of concern. The present study was carried out at Department of Forensic Medicine and Toxicology of B.J.G.M.C and S.G.H. Pune, during November 2015 to September 2017. We have found that in 93.63 % of cases accused was known to the victim. Majority of accused were boyfriends followed by neighbor. The minimum age of accused was 11 years and maximum age was 55 years.